WORKING ENVIRONMENT AND WORK ENGAGEMENT OF HEALTHCARE WORKERS AT TAN PHU GENERAL HOSPITAL, HO CHI MINH CITY, 2026 (Vietnam Journal of Community Medicine, 2026)
Objectives: To assess the work environment, level of work engagement, and associated factors among healthcare workers at Tan Phu General Hospital, in 2026.Subjects and methods: A cross-sectional study was conducted among 435 healthcare workers. Data were collected using a structured self-administered questionnaire. The work environment was measured using the AWS, and work engagement was assessed using the UWES-9. Data were managed with Epidata Manager software and analyzed using Stata 17 software. Multivariable linear regression was performed to identify factors associated with work engagement.Results: The mean age of participants was 34.82 ± 6.89 years, with males accounting for 30.6%. The mean AWS score was 3.49 ± 0.34. The overall UWES-9 score was 4.03 ± 0.86, with mean scores of 4.02 ± 1.01 (vigor), 4.24 ± 0.94 (dedication), and 3.82 ± 0.92 (absorption). Multivariable analysis indicated that years of service, job control, fairness, and value alignment were significantly associated with work engagement, explaining 45.1% of its variance (p < 0.05).Conclusions: Healthcare workers demonstrated a relatively high level of work engagement, which was significantly influenced by workplace conditions. Strengthening organizational resources-particularly enhancing fairness, job control, and value alignment-may serve as effective strategies to sustain motivation and improve workforce performance in healthcare settings.
Keywords: Work environment, work engagement, healthcare workers, job demands-resources.